Galaxy S4 the missing manual - Gralla, Preston (O'Reilly, 2013)
Galaxy S4 is amazing right out of the box, but if you want to get the most of out your S4 or S4 Mini, start here. With clear instructions and savvy advice from technology expert Preston Gralla, you'll learn how to go online, play games, listen to music, watch movies & TV, monitor your health, and answer calls with a wave of your hand. The important stuff you need to know: Be connected. Browse the Web, manage email, and download apps through WiFi or S4's 3G/4G network. Navigate without touch. Use Air Gestures with your hand, or scroll with your eyes using Smart Screen. Find new ways to link up. Chat, videochat, and add photos, video, or entire slideshows to text messages. Get together with Group Play. Play games or share pictures, documents, and music with others nearby. Create amazing images. Shoot and edit photos and videos--and combine images from the front and back cameras. Keep music in the cloud. Use Google Play Music to store and access tunes. Check your schedule. Sync the S4 with your Google and Outlook calendars.
Includes index. - Online resource; title from title page (Safari, viewed Oct. 10, 2013)
Keywords: Samsung Galaxy S (Smartphone); Smartphones; Samsung Galaxy S (Téléphone intelligent); Téléphones intelligents